Administrative oversight in the Peruvian legal system: from heterogeneity to a common regulation - Sánchez Povis, Lucio Andrés (2020)
This article addresses the general conceptual framework of administrative oversight and the heterogeneous development that it had at the regulatory level in the Peruvian system until 2016. To address this heterogeneity, this study recounts the legal attention that this activity has received. On the one hand, under the 1979 Constitution, according to which the administrative oversight had to adjust to the prevailing Entrepreneurial State model in that period. On the other, from the 1993 Constitution to the present day, during which the administrative oversight has not only had to be strengthened and specialized, but has demanded an organizational transformation in the Peruvian State, to the point of collecting common provisions for the exercise of this administrative power in Law No. 27444.